857Data harmonisation of Australian and New Zealand ambulance service datasets. (2nd September 2021) - Eastwood, Kathryn; Johnson, Alison; Jones, Angela; Cameron, Peter; Teede, Helena
Abstract: Background: Australia has eight state-based ambulance services and New Zealand (NZ) has two. Significant variation between their datasets compromises cross-border research opportunities and translation of research to improve patient care. Ambulance data harmonisation has occurred in the United States and United Kingdom however, to-date no data harmonisation has occurred in Australia. This study aims to compare ambulance service variables in Australia and NZ to identify opportunities and barriers for harmonisation. Method: Available 2019 variables were mapped to each other and several international standardized terminology systems to identify variations and similarities in variable names and definitions, and harmonisation opportunities. Results: Four Australian ambulance services used one electronic patient care record (ePCR) system, three used other ePCR systems, one used paper-based records and both NZ services used one ePCR system. Only the NZ services had mapped their variables to two international standardised terminology systems. Barriers to harmonisation included the variables collected, the variable definitions and the variable naming convention. The core variables available for mapping varied and numbered from 27-69. Differences included similar variable names having different definitions, variables that should have different definitions having the same, and naming convention for similar/same variables differing between services. Conclusions: Ambulance service data harmonisation in Australia and NZ is possible and presents significant opportunities for improvement in patient outcomes and performance audit. It would facilitate quality, large-scale, high-impact collaborative national and international research. Key Message: There is an opportunity for Australian and NZ ambulance services to harmonise their data to conduct large scale international research.